2019
DOI: 10.5703/1288284316788
|View full text |Cite
|
Sign up to set email alerts
|

Pack Rust Identification and Mitigation Strategies for Steel Bridges

Abstract: Pack rust or crevice corrosion is a type of localized corrosion. When a metal is in contact with a metal, or even non-metal, the metal starts to corrode, and rust starts to pack in between the surfaces. When significant development of pack rust occurs, it can cause overstressing of bolts and rivets causing them to fail, and it can bend connecting plates and member elements thus reducing their buckling capacity. Thus it is important to mitigate the formation and growth of pack rust in bridges. This study was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Previous studies demonstrated that effective alternatives to mitigate pack rust are required to address the high number of bridges with pack rust in Indiana. It was determined that splice connections required special attention (3,4). Therefore, the main purpose of this study is to test three mitigation approaches that can be implemented in the field to delay additional pack rust development.…”
Section: Purpose and Scope Of The Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that effective alternatives to mitigate pack rust are required to address the high number of bridges with pack rust in Indiana. It was determined that splice connections required special attention (3,4). Therefore, the main purpose of this study is to test three mitigation approaches that can be implemented in the field to delay additional pack rust development.…”
Section: Purpose and Scope Of The Researchmentioning
confidence: 99%
“…It has been observed in the field that pack rust can range from simply staining at the mouth of the crevice to bulging of the overlapping plates to 0.75 in. or more (3,4). In steel bridges, this type of corrosion can be spotted in gusset plates, joints, splice connections, and other connections with bolted and riveted fasteners.…”
Section: Pack Rust On Steel Bridgesmentioning
confidence: 99%
“…Corrosion costs in the infrastructure industry to $ 22.6 billion, of which $ 8.3 billion was spent on road bridges. [3] 1.1 COR-TEN STEEL DESCRIPTIONS These steels defined in the European standard are intended for use in welded, rivets or bolted structures, whose operating temperature is the environment and must have an improved resistance to atmospheric corrosion. [4] These are not intended to be heat treated, except for products that undergo a standardization forming (lamination process in which the final deformation is carried out within a temperature range such that the state of the material is equivalent to that of would be obtained after a normalization treatment and that allows the specified values of the mechanical characteristics to be maintained even after a new normalization treatment).…”
Section: Fig 1 -Corrosion Of Steel Beammentioning
confidence: 99%
“…the buildup of corrosion within the crevice of two adjoining surfaces, as shown inFigure 2.13 Patel and Bowman 2018. …”
mentioning
confidence: 99%
“…Oregon DOT uses a system of mechanical cleaning; the water saturated pack rust is first heated to a temperature range of 250°F to 400°F and then removed mechanically (by hammering the connection plate). In Missouri, a rust penetrating sealer made up of calcium sulfonate is used to mitigate the effects and occurrence of pack rust(Patel and Bowman 2018).…”
mentioning
confidence: 99%